MiR-324-5p reduces viability and induces apoptosis in gastric cancer cells through modulating TSPAN8 - Lin, Hai; Zhou, Ai-Jun; Zhang, Jing-Yu; Liu, Shu-Fang; Gu, Jian-Xiang (Journal of pharmacy and pharmacology, 2018)
The purpose of this study was to further clarify the role and underlying mechanism of miR-324-5p in gastric cancer. The expressions of miR-324-5p and TSPAN8 as determined by qRT-PCR or Western blot were compared between the gastric cancer tissues and normal tissues. Human gastric cancer cell line SGC-7901 was cultured and transfected with miR-324-5p mimic/inhibitor or pcDNA-TSPAN8. The cell survival was assessed by the cell viability and apoptosis. Luciferase reporter gene assays were performed to explore the interaction between miR-324-5p and TSPAN8 in SGC-7901 cells. MiR-324-5p was decreased in human gastric carcinoma tissues (n = 33), but TSPAN8 protein expression was increased in the gastric carcinoma tissues (n = 33). Moreover, miR-324-5p inhibited the viability and induced the apoptosis of gastric cancer cells in vitro. TSPAN8 is a functional target of miR-324-5p in gastric cancer. MiR-324-5p was further confirmed to reduce gastric cancer cell viability and induce apoptosis via downregulating TSPAN8 in SGC-7901 cells in vitro. Additionally, miR-324-5p overexpression markedly inhibited the tumorigenesis of gastric cancer cells in vivo, as shown by the smaller tumour volume compared with the control. This study suggested a novel, probable mechanism of miR-324-5p in gastric cancer context and revealed that miR-324-5p inhibited gastric cancer cell survival by targeting TSPAN8.